Radio advertisement speech style preferences among listeners with different first languages within one country - Altrov, Rene; Pajupuu, Hille; Pajupuu, Jaan; Kiisla, Aet (Frontiers in Communication, 2023)
Objective The goal of the study was to find out if, in a society where there is a large community of people for whom the official state language is a second language, they prefer to listen to state-language radio advertisements in the same performance style as listeners for whom the official state language is their first language. Method An experiment was conducted in Estonia, with two groups: those who spoke Estonian as their first language and those who spoke Russian as their first language and Estonian as their second. Both groups listened to Estonian-language radio advertisements presented by various spokespeople, half of which were performed in a calm style (low arousal) and half in an energetic style (high arousal). They then rated the likability of each performance. Results The results showed that both groups preferred the calm style but there were significant differences in the scores: the first group gave the calm style significantly higher scores than the second group, while the latter scored the energetic style more highly. Conclusion Knowing the advertising style preferences in a society where people have different first languages may allow for better targeting of advertising.